Understanding by Design (UbD) Learning Model for Developing Independent Learning Competencies in a Madrasah Ibtidaiyah - Naila Tazkiyatil Afidah; Asep Herry Hernawan (Khazanah Pendidikan Islam, 2025)
This study aims to develop a learning design utilizing the Understanding by Design (UbD) framework to enhance the self-regulated learning competence of fifth-grade students in Madrasah Ibtidaiyah. The background of this research is rooted in the low level of students’ learning independence, as reflected in their lack of initiative, planning, task execution, and responsibility throughout the learning process. The study employed a Design-Based Research (DBR) approach through four stages: problem identification, solution design, limited implementation, and reflection with design revision. Data were collected triangulatively through questionnaires, observations, written interviews, documentation, and student performance assessments. The developed learning design follows the principles of backward design, focusing on four main aspects of self-regulated learning: initiative, planning, independent task completion, and learning responsibility. The trial results revealed that UbD-based learning had a positive impact on nurturing student independence in affective, cognitive, and psychomotor aspects. Observation data indicated an increase in students’ active engagement and sense of responsibility, while the project-based mini-booklets and reflective journals demonstrated their ability to plan and complete tasks independently. The study concludes that the UbD learning design is effective in supporting the development of students' self-regulated learning competence in Madrasah Ibtidaiyah. This research offers practical contributions in designing contextual and character-oriented learning and reinforces the “Independent” dimension in the Pancasila Student Profile.